Inflammation altered correlation between CYP2C19 genotype and CYP2C19 activity in patients receiving voriconazole - Sylvia D. Klomp; Anette Veringa; Jan‐Willem C. Alffenaar; Mark G. J. deBoer; Lambert F. R. Span; Henk‐Jan Guchelaar; Jesse J. Swen (Wiley, 2024)
Abstract Voriconazole is the cornerstone of the treatment and prevention of fungal infections. While there is a good correlation between CYP2C19 genotype and voriconazole exposure during prophylactic treatment, no correlation was found in patients with invasive aspergillosis. Proinflammatory cytokines result in inhibition of CYP2C19 enzyme activity (and may result in phenoconversion). Here we investigated the relationship between inflammation, CYP2C19 genotype‐predicted‐phenotype, and CYP2C19 activity in patients receiving voriconazole. Data were obtained from two prospective studies investigating voriconazole treatment (NCT02074462 and NCT00893555). Dose‐corrected voriconazole plasma concentration and C‐reactive protein (CRP) were used as proxies for CYP2C19 activity and inflammation, respectively. After data extraction and synthesis, data from 39 patients with paired voriconazole and CRP measurements were available. The distribution of CYP2C19 genotype‐predicted metabolizer phenotypes was 31% intermediate (IM), 41% normal (NM), and 28% rapid metabolizer (RM). During inflammation, dose‐corrected voriconazole levels were increased by 245%, 278%, and 486% for CYP2C19 NMs IMs and RMs, respectively. Patients with moderate or high CRP levels (>50 mg/L) were phenoconverted to a lower metabolizer phenotype irrespective of their CYP2C19 genotype. In a subgroup analysis of eight patients with longitudinal data available with and without inflammation, the pattern of the dose‐corrected voriconazole and CRP measurements were similar, with CYP2C19 activity following decreasing or increasing CRP levels. In conclusion, voriconazole plasma concentrations increase during inflammation due to downregulation of CYP2C19 activity. While this effect appears largest for CYP2C19 RMs, no clinically relevant differences were observed between the CYP2C19 genotypes.